P–089 Paternal age affects the performance of EAU guidelines for genetic testing in infertile men: implications for candidate selection. (6th August 2021) - Ventimiglia, E; Boeri, L; Pozzi, E; Belladelli, F; Fallara, G; Candela, L; Capogrosso, P; Schifano, N; Cignoli, D; Colandrea, G; Cornelius, J; Mattei, A; et al.
Abstract: Study question: We aimed at challenge EAU Guidelines for genetic testing performance in infertile men according to normal vs. advanced paternal age (APA). Summary answer: EAU Guidelines perform better in karyotype analysis (KA) and Y-chromosome microdeletions (YCM) investigation in men above 35 years of age. What is known already: EAU Guidelines for genetic testing in infertile men recommend specific threshold for candidate selection for both KA (<10 million spermatozoa/ml) and YCM (<5 million spermatozoa/ml). However, paternal age is not taken into account for candidate selection in this setting. Study design, size, duration: Data from 2188 infertile men (according to WHO definition) consecutively evaluated at a single academic centre were analysed. Participants/materials, setting, methods: Demographic, clinical and laboratory data were analysed. Semen analyses were based on 2010 WHO criteria. Advanced age was defined as above 35. All men underwent KA and YCM testing. EAU Guidelines were validated in our cohort and according to APA. Specificity, sensitivity, and AUC were estimated for all scenarios. A Wald-type test compared AUC according to APA for KA and YCM. Decision curve analysis (DCA) estimated the benefit of using EAU Guidelines according to APA. Main results and the role of chance: Median (IQR) paternal age was 37 (34–41) years. Advanced paternal age was found in 1306 (60%) of included men. Prevalence of KA and YCM was 4% (48 men) and 1% (13 men), respectively. EAU Guidelines sensitivity, specificity and AUC in the overall population were 85%, 47% and 66% for KA, whereas they were 100%, 57% and 80% for YCM. When stratifying according to APA, EAU Guidelines performed better in men over 35 both in terms of KA and YCM detection. Specifically, AUC for KA detection in men with APA was 70% vs. 63% in younger men (p = 0.04). AUC for YCM detection in men with APA was 82% vs. 79% in younger men (p = 0.03). DCA confirmed higher net benefit in using EAU Guidelines in old vs. young men for the detection of both KA and YCM. Limitations, reasons for caution: It is a retrospective analysis at a single, tertiary-referral academic centre, thus raising the possibility of selection biases. Wider implications of the findings: EAU Guidelines for genetic testing in infertile men perform differentially according to APA. KA and YCM are better detected in older men, likely due to a wider pool of confounding etiological factors in young men. These results suggest the implementation of more accurate predictive models in younger men. Trial registration number: Not applicable